2015
DOI: 10.1189/jlb.3hi1214-584r
|View full text |Cite
|
Sign up to set email alerts
|

Human lung-resident macrophages express CB1 and CB2 receptors whose activation inhibits the release of angiogenic and lymphangiogenic factors

Abstract: Macrophages are pivotal effector cells in immune responses and tissue remodeling by producing a wide spectrum of mediators, including angiogenic and lymphangiogenic factors. Activation of cannabinoid receptor types 1 and 2 has been suggested as a new strategy to modulate angiogenesis in vitro and in vivo. We investigated whether human lung-resident macrophages express a complete endocannabinoid system by assessing their production of endocannabinoids and expression of cannabinoid receptors. Unstimulated human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 56 publications
2
125
0
1
Order By: Relevance
“…Therefore, multicellular interactions in the lung constitute the fibrogenic environment and affect progression of the disease. In the lung, CB 1 R is expressed in different cell populations, including ATII cells (35), bronchial epithelial cells (36), and both resident and infiltrating alveolar macrophages (37). We found a high degree of colocalization of CB 1 R with the ATII cell marker SP-C ( Figure 4B).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, multicellular interactions in the lung constitute the fibrogenic environment and affect progression of the disease. In the lung, CB 1 R is expressed in different cell populations, including ATII cells (35), bronchial epithelial cells (36), and both resident and infiltrating alveolar macrophages (37). We found a high degree of colocalization of CB 1 R with the ATII cell marker SP-C ( Figure 4B).…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, human lung macrophages isolated from lungs adenocarcinoma patients, which display M2-like polarization, do not contain elevated levels of AEA following in vitro exposure to LPS (37). In addition, pulmonary inflammation induced by aerosolized LPS, which is not associated with significant cell damage, exhibited neutrophil infiltration and secretion of inflammatory cytokines but no increase in AEA in BALF (57).…”
Section: Rise In Fibrogenic Cd206mentioning
confidence: 94%
“…However, we show that most leukocytes do not biosynthesize substantial levels of 2‐AG in response to agonists recognized to activate the PLC pathway, either in the absence or in the presence of MAFP. One study showed that human lung macrophages stimulated with LPS synthesize more 2‐AG in the presence of a MAG lipase inhibitor but this increase of approximately 40% is modest compared to the impact MAFP had in our biosynthetic route involving UFAs …”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of 2‐AG by human leukocytes is not well documented. Furthermore, efforts to induce 2‐AG biosynthesis in leukocytes led to 2‐AG levels lower than those required to activate the CB 2 receptor, for which 2‐AG has a Ki of ~145 nM . The classic 2‐AG biosynthetic pathway involves two enzymatic steps.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-C and VEGF-D are crucial for the survival, proliferation, and migration of LECs by engaging VEGFR3 [155]. VEGF-A also influences lymphangiogenesis by recruiting immune cells (e.g., macrophages and mast cells) that produce VEGF-C and VEGF-D [9, 156]. Angiopoietins (ANGPT1 and ANGPT2) also modulate angiogenesis and lymphangiogenesis through the engagement of TIE1 and TIE2 receptors [157].…”
Section: Mast Cells In Angiogenesis and Lymphangiogenesismentioning
confidence: 99%